Catheter-based closure of a large atrial septal defect with inferior rim deficiency using pulmonary vein slide-out assisted implantation technique: a case report. Issue 2 (8th February 2021) - Evola, Salvatore; Triolo, Oreste Fabio; Novo, Giuseppina; Onorato, Eustaquio Maria
Abstract: Background: Transcatheter approach for large and complex atrial septal defects may represent a therapeutic challenge, particularly when the postero-inferior rim is deficient and floppy. Case summary: Here, we describe a successful catheter-based closure of a large (>30 mm) secundum atrial septal defect associated with postero-inferior rim deficiency in a 35-year-old female with congestive heart failure using pulmonary vein slide-out assisted implantation technique. Discussion: Inferior–posterior rim deficiency is a well-known risk factor for device instability or embolization. Transcatheter closure may represent a safe and effective alternative to the traditional surgical approach provided that modified implantation techniques are employed.